Natural resources, consumer prices and financial development in China: Measures to control carbon emissions and ecological footprints. (September 2022) - Hussain, Muzzammil; Wang, Wei; Wang, Yiwen
Abstract: China's natural resources are a major factor in its rapid financial development. In this race of development, the environment is compromised and China became the top polluted country in the world. A sustainable environment is required for sustainable development. Unlike others, we examine CO2 emissions and ecological footprint (EFP) to compare the role of natural resource rents (NRR), consumer prices (CP), financial development (FD), and population density (PD) in China. To empirically estimate the proposed linkages, the latest econometric techniques are used i. e, "Stationarity and co-integration tests with structural breaks and the autoregressive distributed lag models". Findings report U-shaped Environmental Kuznets Curve (EKC) for CO2 emissions and EFP, which means GDP is helping to control CO2 emissions and EFP in China. However, natural resources, consumer prices, and population density are increasing environmental degradation. Moreover, financial development is helpful to decrease carbon emissions and ecological footprints. China needs to re-consider the policy regarding consumer prices, dense inhabitant population and use of natural resources. Highlights: China's natural resources, consumer prices, financial development, and CO2 emissions are re-estimated. Carrion's unit root and Maki's co-integration with multiple breaks are applied. Time Breaks in 1991, 2001, and 2009 substantially influenced pollution in China. Natural resources, consumer prices, and population density are increasing carbon emissions and ecological footprints. Financial development is supportive to control pollution.